Hydrolysis Kinetics of Bacterial Cellulose Using Sodium Hydroxide - Panjaitan, Jabosar Ronggur Hamonangan; Padang, David Andrian; Fatchurohman, Aziz; Ramadhan, Fourka Fitra (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2023)
The hydrolysis reaction is a rupture reaction of reactants with water which is generally used to produce useful derivative products and can be reviewed for kinetics as a basis for reactor design. Nata or bacterial cellulose is a compound consisting of pure cellulose and water so that it can be hydrolyzed to produce various cellulose degradation products. This research examined the kinetic hydrolysis of bacterial cellulose using a sodium hydroxide catalyst. This study aimed to determine the kinetic parameters of the nata hydrolysis reaction using a base sodium hydroxide catalyst. The results showed higher temperatures and longer hydrolysis time performed better in hydrolysis reactions. The hydrolysis kinetics in this study were divided into two types, Type 1 hydrolysis kinetics which used the wet weight of bacterial cellulose, and Type 2, which used the dry weight of bacterial cellulose. From the calculation results, the order of bacterial cellulose hydrolysis reaction ranges from 5 – 6, with the kinetic constants of Type 1 hydrolysis kinetics at 40oC, 60oC, and 80oC were 0.000012, 40,255.4, and 299,839 min-1. In comparison, the reaction constants of Type 2 hydrolysis kinetics at 40oC, 60oC, and 80oC were 0.516851, 1.124119, and 2.408972 min-1. The activation energy of Type 1 hydrolysis kinetics was 558.3932 kJ/mol, and Type 2 hydrolysis kinetics was 35.31205 kJ/mol. The difference in kinetic parameter values for Types 1 and 2 will be a reference in designing a nata hydrolysis reactor from wet and dry nata reactants to produce various cellulose degradation compounds.ABSTRAKReaksi hidrolisis merupakan reaksi pemecahan reaktan dengan air yang umumnya dilakukan untuk memproduksi produk – produk turunan bermanfaat dan dapat ditinjau kinetikanya sebagai dasar dalam perancangan reaktor. Nata atau selulosa bakteri merupakan senyawa yang terdiri dari selulosa murni dan air sehingga dapat dihidrolisis untuk menghasilkan berbagai senyawa degradasi selulosa. Pada penelitian ini diteliti kinetika hidrolisis selulosa bakteri menggunakan katalis natrium hidroksida. Tujuan dari penelitian ini adalah untuk menentukan parameter kinetika reaksi hidrolisis nata menggunakan katalis basa natrium hidroksida. Hasil penelitian menunjukkan bahwa semakin tinggi suhu dan lama waktu hidrolisis akan meningkatkan kinerja reaksi hidrolisis. Kinetika hidrolisis pada penelitian ini terbagi dua tipe yaitu kinetika hidrolisis Tipe 1 yang menggunakan berat basah selulosa bakteri dan dan Tipe 2 yang menggunakan berat kering selulosa bakteri. Dari hasil perhitungan diperoleh orde reaksi hidrolisis selulosa bakteri berkisar antar 5 – 6 dengan konstanta reaksi kinetika hidrolisis Tipe 1 pada suhu 40oC, 60oC dan 80oC berturut – turut adalah 0,000012; 40.255,4; dan 299.839 min-1. Sedangkan konstanta reaksi kinetika hidrolisis Tipe 2 pada suhu 40oC, 60oC dan 80oC berturut – turut adalah 0,516851; 1,124119; dan 2,408972 min-1. Energi aktivasi kinetika hidrolisis Tipe 1 sebesar 558,3932 kJ/mol, dan energi aktivasi kinetika hidrolsis Tipe 2 sebesar 35,31205 kJ/mol. Perbedaan nilai parameter kinetika pada Tipe 1 dan 2 akan menjadi acuan dalam perancangan reaktor hidrolisis nata berbahan baku nata basah dan kering untuk memproduksi berbagai senyawa degradasi selulosa.